POTENSI BIOINSEKTISIDA FORMULASI CAIR BERBAHAN AKTIF Beauveria bassiana (BALS.) VUILL DAN Metarhizium sp. UNTUK MENGENDALIKAN WERENG COKLAT PADA TANAMAN PADI - Irwan, Irwan (JSTT, 2016)
The Potential of Formulation of Liquid biopesticide active substance derived from Beauveria bassiana (BALS.) VUILL and Metarizhium sp. To control the brown rice plant hopper. This study aims to assess the potential of B.bassiana fungus and Metarizhium sp. to control the brown rice plant hopper. The research was carried on on the Field from March to May 2013. This study used a completely randomized design consisting of B.bassiana at concentrations 107 (A1), 108 (A2), and 109 (A3). and Metarizhium sp. At concentrations 107 (B1), 108 (B2), and 109 (B3). with three replicates for each treatment. The results showed that B.bassiana was faster at controlling brown rice planthopper nymphs compared to Metarizhium sp, however, both showedÂ  very promising results .fastest LT50 was observed in B.bassiana with a time of 24.87 hours at a concentration of 107 and in Metarizhium sp. causing the death of test insects within 25.67 hours at a concentration of 107